NILAI-NILAI PENDIDIKAN KARAKTER DALAM KABA SABAI NAN ALUIH KARYA M.RASYID MANGGIS DT. RAJO PENGHULU DAN IMPLIKASINYA DALAM PEMBELAJARAN TEKS HIKAYAT KELAS X SMA - Maresta, Nella; Abdurrahman, Abdurrahman (Universitas Negeri Padang, 2019)
ABSTRACTÂ The data of this study consisted of words, sentences and discourses that featured events and figures that changed the values of character education included in Kaba Sabai Nan Aluih Karya M. Rasyid Manggis Dt. Rajo Penghulu. The technique of collecting this research data, namely reading and understanding, inventorying, and retrieving data relating to character education values in Sabai Nan Aluih's kaba and adoption when reading appreciation. The technique of analyzing the data of this study, namely data that has been collected and classified, is then analyzed based on theory. The method used is descriptive method, according to the purpose of the study. Based on the results of the study, the values of character education studied in kaba Sabai Nan Aluih by M. Rasyid Manggis Dt. Rajo Penghulu found. First, data that contains the value of honest character education. Second, the data that contains the value of the education of the character of hard work. Third, data that contains the value of Mandiri character education. Fourth, data that contains the value of Democratic character education. Fifth, the data containing the values of peace-loving character education. Sixth, the data that contains the value of social care education. Seventh, the data that contains the value of character education is responsible.Â Kata kunci:Â Nilai Pendidikan Karakter, Saga, Kaba